A THEORETICAL PERSPECTIVE ON DIGITALIZATION’S ROLE IN ENHANCING ESG AND GREEN FINANCE - DUPIR MIHAI (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
In the landscape of sustainable finance, digitalization is increasingly pivotal in advancing Environmental, Social, and Governance (ESG) goals and facilitating green finance. As financial markets prioritize sustainability, integrating digital technologies offers unprecedented opportunities to streamline ESG-related processes, enhance transparency, and improve accountability. This article examines the transformative role of digital tools—such as blockchain, artificial intelligence, and big data—in empowering stakeholders across the financial spectrum, from institutional investors to individual consumers, to make more informed and sustainable choices. This study employs a qualitative research approach, drawing on specialized literature and case studies to analyze the role of digitalization in advancing ESG and green finance. A comprehensive review of academic publications, industry reports, and policy papers provides a theoretical foundation, while real-world case studies illustrate the practical applications of digital tools such as blockchain, artificial intelligence, and big data in sustainable finance. By enabling real-time data tracking, digitalization addresses key challenges in ESG reporting, such as the verification of corporate environmental claims and the identification of greenwashing practices. Additionally, artificial intelligence aids in analyzing vast datasets to uncover sustainability patterns, offering investors deeper insights into ESG performance and risk exposure. Furthermore, digital transformation extends beyond reporting. Through Fintech innovations, digitalization is democratizing access to green finance products, facilitating micro-investments in sustainable initiatives, and lowering the barriers for global participation in eco-friendly financial products. This integration not only reinforces corporate commitment to sustainability but also aligns market incentives with global climate objectives, promoting a circular economy. ESG considerations have become mainstream in financial decision-making, and the intersection of digitalization and green finance holds significant potential to drive systemic change toward a sustainable future. By leveraging these technologies, stakeholders can contribute to a robust, transparent, and accountable financial ecosystem that aligns with long-term environmental goals